The production of isolated photons in PbPb and pp collisions at $$ \sqrt{s_{\mathrm{NN}}} $$ = 5.02 TeV - Sirunyan, Albert M.; Tumasyan, Armen; Jeitler, Manfred; Oliveira Martins, Carley; Choi, Junho; Jeon, Sihyun; Kim, Junho; Kim, Jae Sung; Lee, Haneol; Lee, Kyeongpil; Lee, Sangeun; Nam, Kyungwook; et al. (Springer Science and Business Media LLC, 2020)
Abstract The transverse energy ($$ {E}_{\mathrm{T}}^{\upgamma} $$ E T γ ) spectra of photons isolated from other particles are measured using proton-proton (pp) and lead-lead (PbPb) collisions at the LHC at $$ \sqrt{s_{\mathrm{NN}}} $$ s NN = 5.02 TeV with integrated luminosities of 27.4 pb−1 and 404 μb−1 for pp and PbPb data, respectively. The results are presented for photons with 25 <$$ {E}_{\mathrm{T}}^{\upgamma} $$ E T γ < 200 GeV in the pseudorapidity range |η| < 1.44, and for different centrality intervals for PbPb collisions. Photon production in PbPb collisions is consistent with that in pp collisions scaled by the number of binary nucleon-nucleon collisions, demonstrating that photons do not interact with the quark-gluon plasma. Therefore, isolated photons can provide information about the initial energy of the associated parton in photon+jet measurements. The results are compared with predictions from the next-to-leading-order jetphox generator for different parton distribution functions (PDFs) and nuclear PDFs (nPDFs). The comparisons can help to constrain the nPDFs global fits.
Keywords: transverse energy: energy spectrum; p p: scattering; heavy ion: scattering; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; [PHYS.NEXP] Physics [physics]/Nuclear Experiment [nucl-ex]; GeV-cms; binary; FOS: Physical sciences; parton: distribution function; QC770-798; [PHYS.NEXP]Physics [physics]/Nuclear Experiment [nucl-ex]; photon: hadroproduction; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); Hadron-Hadron scattering (experiments); Heavy-ion collision; Nuclear and particle physics. Atomic energy. Radioactivity; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; photon: jet; Nuclear Experiment (nucl-ex); info:eu-repo/classification/ddc/530; impact parameter: dependence; Nuclear Experiment; quark gluon: plasma; lead; Particle physics; Large hadron collider; CMS; CMS; Physics; ddc:530; nucleus; higher-order: 1; perturbation theory: higher-order; Large hadron collider; photon: energy spectrum; CERN LHC Coll; Photon production; photon: rapidity; Particle physics; experimental results